Sukses versus Gagal: Pilihan di antara Proses dan Protes - Hotma Enzelina Saragih; Masduki Asbari; Anisa Agustiana; Aina Winda Mareta; Siti Indah Nurcahyani (AGUSPATI RESEARCH INSTITUTA, 2024)
This journal aims to emphasize the importance of process in every effort to achieve success rather than many useless protests and also aims to understand and practice further regarding viewing methods. This journal uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from Helmy Yahya's YouTube channel entitled